Extending the concept of total pain to cancer survivorship - Krawczyk, Marian; Solbrække, Kari Nyheim; Thoresen, Lisbeth (Frontiers in Sociology, 2025)
More people are surviving cancer than ever before. While there is a growing body of research on quality of life in cancer survivorship, we still do not have a good understanding of the lived complexities that many people experience after successful treatment. Inspired by the literature on existential concerns in cancer survivorship, we consider how the concept of ‘total pain’, which emerged from the contemporary hospice movement, may be useful to think about experiences of suffering in cancer survivorship, using interviews from a Norwegian research project Rethinking Cancer Survivorship. We find that the concept of total pain encapsulates concerns for existential suffering and also has unique features which offer new forms of understanding and action. This includes its origins within cancer care; how it addresses the individual as a whole and re-centres the body; its reliance on and recognition of the limits of narrative; how it attends to relationality; and how the concept may afford unique insights for service development. Dying from cancer and surviving cancer are different processes, but total pain can serve as a useful conceptual compass to orient our understandings of those who experience this illness, regardless of disease outcome.